Continuous flow adsorption of ciprofloxacin by using a nanostructured chitin/graphene oxide hybrid material - González, Joaquín Antonio (2018)
A novel nanostructured material was successfully developed by combining a chitin matrix with graphene oxide nanosheets (Chi:nGO) and then used for the continuous flow adsorption of ciprofloxacin. The spectroscopic characterization indicated that none covalent interaction between both components would be occurring and the introduction of nGO did not interfere in chitin nanostructure rearrangement during gelling and later drying. SEM images and Mercury Intrusion Porosimetry results showed a wide pore size distribution ranging from nano to micrometers. The continuous flow adsorption was observed to be dependent on the pH which affects the electrostatic interaction. The flow rate, Na+ concentration and water hardness were evaluated to describe the adsorption process. The resistance to alkali allowed to regenerate and reuse the column for subsequent adsorption cycles. Finally, ciprofloxacin spiked real water samples were assessed and the results confirmed that the medium pH was the main parameter that defines the adsorption behavior.